2017
DOI: 10.1097/rlu.0000000000001534
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Added Value of 99mTc-MIBI SPECT/CT to Conventional Cross-Sectional Imaging in the Characterization of Enhancing Solid Renal Masses

Abstract: Preoperative Tc-MIBI SPECT/CT enhances the performance of conventional imaging, improving the characterization of benign histologies and lowering the possibility of misclassification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 31 publications
(55 reference statements)
0
36
0
Order By: Relevance
“…18 A secondary analysis of this study illustrated that incorporating 99m Tc-sestamibi SPECT/CT into the pre-operative work-up of renal lesions significantly augmented confidence in characterizing renal masses as benign or malignant. 19 Following these reports, investigators at the Karolinska University Hospital in Stockholm, Sweden found similar results in a study of 27 patients with 31 tumours imaged with 99m Tc-sestamibi SPECT/CT prior to either surgery or biopsy. In this study, 11/12 (91.6%) oncocytomas and 3/3 (100%) HOCTs were identified with this imaging test, with only two false positives (one papillary RCC that was described as having "slight" uptake and one angiomyolipoma).…”
mentioning
confidence: 73%
“…18 A secondary analysis of this study illustrated that incorporating 99m Tc-sestamibi SPECT/CT into the pre-operative work-up of renal lesions significantly augmented confidence in characterizing renal masses as benign or malignant. 19 Following these reports, investigators at the Karolinska University Hospital in Stockholm, Sweden found similar results in a study of 27 patients with 31 tumours imaged with 99m Tc-sestamibi SPECT/CT prior to either surgery or biopsy. In this study, 11/12 (91.6%) oncocytomas and 3/3 (100%) HOCTs were identified with this imaging test, with only two false positives (one papillary RCC that was described as having "slight" uptake and one angiomyolipoma).…”
mentioning
confidence: 73%
“…Molecular imaging with 99m technetium–sestamibi single photon emission computed tomography/computed tomography ( 99m Tc-MIBI SPECT/CT) has also been used to differentiate oncocytomas and indolent hybrid oncocytic/chromophobe tumours from other more aggressive malignant small renal tumours. The former contain numerous and dense cellular mitochondria and therefore demonstrate “hot” radiotracer uptake relative to the ipsilateral renal parenchyma, whereas the latter appear “cold” [ 70 , 71 ]. Sheikhbahaei et al evaluated the diagnostic accuracy of standard pre-operative CT, MRI and 99m Tc-MIBI SPECT/CT in 48 patients with small renal masses undergoing partial or radical nephrectomy.…”
Section: Resultsmentioning
confidence: 99%
“…Sheikhbahaei et al evaluated the diagnostic accuracy of standard pre-operative CT, MRI and 99m Tc-MIBI SPECT/CT in 48 patients with small renal masses undergoing partial or radical nephrectomy. The area under the receiver operator characteristic curve for the differentiation of benign from malignant masses was 0.60 for CT and MRI alone, increasing to 0.85 with the addition of 99m Tc-MIBI SPECT/CT [ 71 ]. Quantitative techniques for image analysis may enable increased accuracy and use of 99m Tc-MIBI SPECT/CT in future [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of these nine patients, pathology report was compatible with oncocytoma in seven patients and chromophobe RCC in two patients. Five patients with negative Tc-99m MIBI SPECT/CT were confirmed to have RCC in the postoperative period (32).…”
Section: Tc-99m Myocardial Perfusion Imaging Test Spect/ctmentioning
confidence: 99%